POLICY OF HUMAN RESOURCE MANAGEMENT OF JSC UKRZALIZNYTSYA AND WAY OF ITS IMPROVEMENT - Krikhtina , Yulia; Savchenko , Olena; Tkachenko , Inna (Theory and Practice of Public Administration, 2019)
The article reviews рolicy of human resource management of JSC “Ukrzaliznytsya” and outlines ways to improve it in the conditions of corporateization of the industry. The HR policy is an integral part of the Company’s general policy. Its purpose is to ensure an optimal balance between updating and maintaining of the Company’s personnel quality during its development in accordance with the needs, requirements of the current legislation, the state of the labour market, and the Company’s Development Strategy. In 2018, Ukrzaliznytsia implemented effective directions of HR policy: the systems of search and selection, evaluation, training, and development of personnel. The Company gives priority to the development of motivational mechanisms that increase the employees’ investment in and satisfaction with the work. The Company studies and implements international practices in applying tangible and intangible incentives. Notably, Ukrzaliznytsia develops and implements professional development programmes (talent pool, mentoring, career development, advanced training and retraining of employees, and internal coaching). Ukrzaliznytsia’s management is responsible for implementation of the HR policy. The policy efficiency and effectiveness are ensured by the heads of personnel vertical units. The Company extensively cultivates the corporate culture and promotes the development of human resources through the introduction of an HR-school. Ukrzaliznytsia’s top management is responsible for the compatibility of the HR policy principles and areas with the Company’s development goals and Strategy. Summarizing the main directions of the рolicy of human resource management of JSC “Ukrzaliznytsya”, the ways of its improvement should be outlined: improve the remuneration policy; implement a performance evaluation policy for the top management, heads of regional branches and affiliates, their deputies, chief engineers, and chief accountants of regional branches and affiliates; implement a performance-based bonus policy; provide phased automation of management of key performance indicators (efficiency); develop and implement competency frameworks; implement candidate pool programmers; provide phased automation of personnel training and development, as well as a training planning and reporting system; implement a distance learning system. Thus, the рolicy of human resource management should be aimed at achieving the strategic goals of JSC “Ukrzaliznytsya”and, first of all, increasing the financial and economic efficiency of the company’s activities. To facilitate this process, we need: expansion of analytical and planning functions aimed at making advanced, forward-looking solutions; active coordination with other units and services; implementation of a set of measures to actively attract all employees to achieve the planned economic indicators based on new management approaches and the introduction of modern technologies.